2006
DOI: 10.1002/jor.20254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of knee simulator loading and alignment variability on predicted implant mechanics: A probabilistic study

Abstract: Inherent variability in total knee arthroplasty loading and alignment, present in vivo and in simulator testing, may ultimately influence polyethylene tibial insert wear and long-term performance. The effect of this variability was quantified on implant kinematics and contact mechanics during simulated gait loading conditions using semi-constrained and unconstrained fixed bearing, cruciate retaining implants. A probabilistic finite element model of the Stanmore knee wear simulator was utilized to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Overall, the general trends of finite element computations were well compared with the previously 177 published experimental and computational literature for the fixed-bearing cruciate retaining implants [38][39][40][41]. …”
Section: Validation 176mentioning
confidence: 86%
See 1 more Smart Citation
“…Overall, the general trends of finite element computations were well compared with the previously 177 published experimental and computational literature for the fixed-bearing cruciate retaining implants [38][39][40][41]. …”
Section: Validation 176mentioning
confidence: 86%
“…Penalty based contact 61 condition was specified at the tibia insert and femoral component interface with a friction coefficient of 0.04 62 [37]. 63 Kinematics and contact mechanics were calculated based on a computational model of Stanmore knee 64 simulator [38][39][40][41]. Stanmore simulator is a well-established load-controlled knee simulator in which in vivo 65 environment of knee joint is replicated through applying forces and moments to femoral and tibial 66 components [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Wear of tibial polyethylene component depends, among various other factors, on load distributions, component geometry and kinematics of the knee (Laz, et al, 2006, McEwen, et al, 2005. Increased sliding, particularly combined anteroposterior and mediolateral sliding, at the contact interface has been associated with increased wear (Blunn, et al, 1991, Fisher, et al, 2006, McEwen, et al, 2005, Todo, et al, 1999.…”
Section: Discussionmentioning
confidence: 99%
“…This also makes the prosthesis more constrained. Laz et al [9] showed more AP laxity for an unconstrained prosthesis compared to a semi-constrained prosthesis. Since 1998 we started to use a ligament guided knee system (balanSys TM ) with a calibrated tensor and a relatively dished insert.…”
Section: Introductionmentioning
confidence: 99%